Macrophage migration inhibition with mouse tumor antigens: Properties of serum and peritoneal cells during tumor growth and after tumor loss - Halliday, W.J. (Cellular immunology, 1972)
Sera and peritoneal cells (PC) were obtained from mice bearing primary Moloney virus-induced tumors or transplanted chemically induced tumors (“progressor” mice) and from mice in which these tumors had spontaneously regressed or had been surgically removed (“regressor” mice). No stimulus was given to produce peritoneal exudates. PC from the two types of tumor-treated animals were distinguishable. “Regressor” cells had their migration in culture inhibited by the corresponding soluble tumor antigen, whereas “progressor” cells did not. Mixtures of the two kinds of PC were not inhibited. “Progressor” PC produced a soluble substance in vitro which could block the normal inhibition of “regressor” cells. Sera from the two types of mice were also different. “Progressor” serum blocked the migration inhibition usually found with “regressor” PC. “Regressor” serum not only lacked this property but was able to unblock “progressor” PC, so that mixtures of the latter cells with this serum were inhibited by tumor antigen. Macrophage migration inhibition thus revealed cellular immunity and humoral factors analogous to those found by other techniques in animals and human subjects exposed to tumor antigens.